The Influence of Boycott and Brand Image on KFC Purchase Decisions: The Moderating Role of Religiosity among Muslim Consumers in North Sumatra - Siagian, Riza Rasyid; Batubara, Maryam; Rahmani, Nur Ahmadi Bi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study examines the influence of boycott and brand image on the purchase decision of KFC products, with religiosity as a moderation variable in the Muslim community in North Sumatra. The survey was conducted on 100 Muslim respondents according to the research criteria. The analysis used Moderated Regression Analysis (MRA) with SPSS version 27. The results showed that: First, boycotts had a negative and significant effect on purchasing decisions, suggesting that the stronger the motivation of consumers to boycott, the lower their tendency to buy KFC products. Second, brand image also has a significant effect, where a positive brand image can increase consumers' intentions and decisions to make purchases. Third, simultaneously, these two variables (boycott and brand image) together contribute significantly to purchasing decisions, which means that consumers' decisions in purchasing KFC products are influenced by a combination of the two. Fourth, religiosity has been shown to moderate the relationship between boycott and brand image on purchasing decisions. In consumers with high levels of religiosity, the influence of boycotts becomes stronger in lowering purchasing decisions, while the influence of brand image becomes greater in driving purchases. This is evident from the regression equation Y = α + β1X1 + β2X2 + β3X3 + β4Z + β5X1Z + β5X2Z + β5X3Z + e. Overall, a coefficient of determination (R²) of 0.674 indicates that 67.4% of the variation in purchasing decisions can be explained by a combination of boycotts, halal labels, and brand imagery, while the remaining 32.6% the rest is influenced by other factors.